2020
DOI: 10.1515/tjb-2019-0292
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of laboratory results in children with acute appendicitis

Abstract: BackgroundThe correct diagnosis rate in acute appendicitis (AA) is between 72 and 94% despite advanced laboratory and radiologic examinations. This study was conducted to determine the effectiveness of laboratory parameters in the diagnosis of children with appendicitis.Materials and methodsPatients who underwent appendectomy were divided as AA (subdivided into two groups as perforated and non-perforated) and without appendicitis. White blood cell (WBC), neutrophil-to-lymphocyte ratio (NLR), red cell distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Pooling the data (Figure 2) using the random effects model demonstrated no statistically significant difference in the RDW values (WMD = 0.03, 95% CI = (−0.46, 0.52), and p = 0.91) between AA and healthy controls. This outcome was reported by 11 studies [3,30,32,[37][38][39][40]42,43,46,47]. The RDW values of 2590 patients with AA and 983 non-AA cases were compared.…”
Section: Methodological Quality Assessmentmentioning
confidence: 85%
See 1 more Smart Citation
“…Pooling the data (Figure 2) using the random effects model demonstrated no statistically significant difference in the RDW values (WMD = 0.03, 95% CI = (−0.46, 0.52), and p = 0.91) between AA and healthy controls. This outcome was reported by 11 studies [3,30,32,[37][38][39][40]42,43,46,47]. The RDW values of 2590 patients with AA and 983 non-AA cases were compared.…”
Section: Methodological Quality Assessmentmentioning
confidence: 85%
“…One of them did not mention the RDW values and was further excluded. Finally, fifteen studies were included in the final meta-analysis [3,[30][31][32][37][38][39][40][41][42][43][44][45].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This retrospective study from Turkey on 186 children with confirmed AA showed no significant difference in the MPV values ( p = 0.536) between AA and non-AA groups [ 23 ]. The study also evaluated the role of other laboratory results like WBC, NLR, RDW, CRP, and procalcitonin levels.…”
Section: Resultsmentioning
confidence: 99%
“…The average Downs and Black scores for the included studies ranged from 24–28. The studies by Tartar et al and Tuncer et al had the minimum and maximum scores, respectively [ 19 , 23 ]. The inter-observer agreement was almost perfect (Kappa = 0.928, p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation